Intraamniotic inflammation and umbilical cord blood interleukin-6 concentrations in pregnancies complicated by preterm prelabor rupture of membranes. (18th April 2017) - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Soucek, Ondrej; Stepan, Martin; Bestvina, Tomas; Spacek, Richard; Jacobsson, Bo; Cobo, Teresa; Kacerovsky, Marian
Abstract: Objective : To evaluate umbilical cord blood interleukin (IL)-6 concentrations and the occurrence of fetal inflammatory response syndrome (FIRS) with respect to microbial invasion of the amniotic cavity (MIAC) and/or intraamniotic inflammation (IAI) in pregnancies complicated by preterm prelabor rupture of membranes (PPROM). Methods : One-hundred-eighty-eight women with singleton pregnancies complicated by PPROM between gestational ages of 24 + 0 and 36 + 6 weeks were included in the study. Blood samples were obtained by venipuncture from the umbilical cord after the delivery of the newborn. The umbilical cord blood IL-6 concentrations were evaluated using ELISA kits. FIRS was defined as umbilical cord blood IL-6 > 11 pg/mL. Result : Women with MIAC and IAI had higher IL-6 concentrations than women without these complications (with MIAC: median 18.1 pg/mL versus without MIAC: median 5.8; p < 0.0001; with IAI: median 32.9 pg/mL, versus without IAI: median 5.8; p < 0.0001). Women with IAI with MIAC and women with IAI without MIAC had the highest umbilical cord blood IL-6 concentrations (medians: 32.6 and 39.4 pg/mL) and rates of FIRS (78% and 67%). Conclusions : IAI was associated with the highest umbilical cord blood IL-6 concentrations and rate of FIRS independent of the presence or absence of MIAC.